The Influence Of Green Marketing Environmental Awareness And Purchasing Interest On Decisions To Purchase Aqua Gallon Drinking Water In The City Of Yogyakarta - Slamet Riyadi; Rinaldi (Penerbit Hellow Pustaka, 2024)
This research aims to determine the influence of green marketing, environmental awareness, and purchasing interest on the decision to purchase aqua gallon bottled drinking water in the city of Yogyakarta. The analysis test tool used is SmartPLS V.4 with the SEM (Structural Equation Modeling) analysis method. With the results, namely: 1. Green marketing (X1) has no influence on purchasing decisions regarding (Y). This is proven by the results of the p value 0.164 > 0.05, the t statistical significance value 1,390 < 1.96 (5%). 2. Environmental awareness (X2) has no influence on purchasing decisions regarding (Y). This is proven by the results of the p value 0.519 > 0.05, the t statistical significance value 0.645 < 1.96 (5%), which means that the environmental awareness variable (X2) does not have a positive effect on purchasing decisions (Y). 3. Purchase interest (X3) has a positive influence on purchasing decisions regarding (Y). This is proven by the results of the p value 0.000 < 0.05, the t statistical significance value 5,413 > 1.96 (5%).